KATA KETERANGAN FREKUENSI DALAM BAHASA INGGRIS DAN BAHASA TONDANO (Suatu Analisis Kontrastif) - KATUPAYAN, STEVANI NATALIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT The title of this study is adverb of frequency in English and Tondano language. The aims of this study is an attempt to identify, to analyze, and to describe about the form, position and meaning in English and Tondano language and to find out the similarities and differences of both languages by using the theory of Lyons (1975:325-326), Michael Swan (2005:16-23) and Murthy (1998:180-181) In this study, the English data was taken from some English Linguistics and grammar books and the Tondano language was taken by interviewing some informants. The method that has been applied in this study is contrastive analysis. The data of this study was analyzed descriptively. The result of this study shows that both languages have differences and similarities. Based on forms, the adverbs of frequency in both languages are bound and free forms, based on their positions they are in front, middle and end positions. The meaning of both languages are just the same that describe how often an action is performed. The differences of these languages are found in the forms, positons and meaning. The adverbs of frequency in English language are formed by adding clitics {-ly} and in Tondano language are formed by adding affix {-i} and clitics {-la}, {-mou} and {-te}. The positions of adverb of frequency in English language are found in front, middle and end positions whereas in Tondano language are only in the front and middle positions. Â  Keywords: adverb of frequency, contrastive analysis, English, Tondano, language.